2021
DOI: 10.1063/5.0047977
|View full text |Cite
|
Sign up to set email alerts
|

Domains and domain dynamics in fluorite-structured ferroelectrics

Abstract: Ferroelectricity in fluorite-structured ferroelectrics such as HfO2 and ZrO2 has been attracting increasing interest since its first publication in 2011. Fluorite-structured ferroelectrics are considered to be promising for semiconductor devices because of their compatibility with the complementary metal–oxide–semiconductor technology and scalability for highly dense information storage. The research on fluorite-structured ferroelectrics during the first decade of their conceptualization has been mainly focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 176 publications
2
58
0
Order By: Relevance
“…In a voltage sweep range of −6 to 6 V, a ferroelectric capacitor exhibited positive and negative remnant polarization of 15.1 and −14.1 C/cm 2 , respectively. These results confirmed that HfZrO x had ferroelectric characteristics and that its polarization characteristics could be adjusted by changing the amplitude of the applied voltages (39,40). We fabricated synaptic transistor arrays by integrating FeTFTs with IZO and HfZrO x (Fig.…”
Section: Parallel Programming Of a Ferroelectric Synaptic Transistor ...supporting
confidence: 69%
“…In a voltage sweep range of −6 to 6 V, a ferroelectric capacitor exhibited positive and negative remnant polarization of 15.1 and −14.1 C/cm 2 , respectively. These results confirmed that HfZrO x had ferroelectric characteristics and that its polarization characteristics could be adjusted by changing the amplitude of the applied voltages (39,40). We fabricated synaptic transistor arrays by integrating FeTFTs with IZO and HfZrO x (Fig.…”
Section: Parallel Programming Of a Ferroelectric Synaptic Transistor ...supporting
confidence: 69%
“…[249] Therefore, the polarization switching pathways of the polar o-phase were investigated by several researchers. [384][385][386][387][388] The initial investigation showed that the energy barrier between two different polarization states (i.e., ±P) in HfO 2 is ≈ 20 times higher than that of the conventional BaTiO 3 ferroelectric films (Figure 20a). [360] It has been reported that the o-HfO 2 could be switched by moving four oxygen ions upward or downward along the polar c-axis.…”
Section: High E Cmentioning
confidence: 99%
“…[3][4][5][6][7][8] The origin of ferroelectricity has been studied extensively due to the formation of an otherwise unstable, polar orthorhombic phase, stabilized by dopants, defects, and kinetic factors during growth. [9][10][11][12][13][14][15][16] The polarization switching behavior of ferroelectric materials is a decisive factor in the operation of ferroelectric devices. The coercive field (E c ) and remnant polarization (P r ) of a ferroelectric material are the defining parameters for its hysteretic behavior.…”
Section: Introductionmentioning
confidence: 99%